Impact of mean state on intermodel spread of western North Pacific anomalous anticyclone during El Niño mature winter in CMIP6 models - Jiahao Lu; Xieyuan Wang; Yuhan Gong; Zhiheng Chen; Zongci Huang; Xu Chen (Scientific Reports)
Abstract The impact of the mean state on simulated western North Pacific anomalous anticyclone (WNPAC) during El Niño mature winter was studied through the diagnosis of 45 historical climate experiments from the CMIP6. The result indicates that in addition to the model-simulated El Niño-related sea surface temperature anomalies (SSTA), the atmospheric mean state also plays an important role in modulating the intermodel spread of WNPAC, especially the intensity and zonal location. On one hand, the central Pacific mean-state precipitation/moisture fields can modulate the western North Pacific (WNP) thermal condition responded to the SST forcing in the Niño-3.4 region through a local circulation-convective feedback, and thus affecting the intensity of WNPAC. On the other hand, the mean-state meridional vorticity gradient in the WNP and the westward-extended central Pacific warming may have acted together to regulate the WNPAC zonal location.